PEMBELAJARAN MATEMATIKA YANG MENYENANGKAN MENGGUNAKAN MEDIA KARTU BILANGAN, DI SD - Yohanes Paulus Duru Payong; Yakobus Leaq; Yohanes Karlosatius Djawa; Maria Goreti Rona; Hamida Lango Belen; Maria Melania Empit (Bajang Institute, 2024)
Education is a planned basis for creating a learning atmosphere and learning process so that students actively develop their potential to have spiritual strength, self-control, personality, intelligence, morals, life knowledge, general strengthening and the skills needed to develop their potential in the community. To make learning mathematics more enjoyable, you can use various kinds of learning media, one of which is number card media, at SDI Mbongawani. With the media of number cards, it is very easy for students during the learning process, so that students can more easily understand and be able to solve problems related to learning mathematics in everyd